2005
DOI: 10.1021/cm050755a
|View full text |Cite
|
Sign up to set email alerts
|

Optically Active Electrochromism of Poly(3,4-ethylenedioxythiophene) Synthesized by Electrochemical Polymerization in Lyotropic Liquid Crystal of Hydroxypropyl Cellulose/Water: Active Control of Optical Activity

Abstract: The electrochemical polymerization of 3,4-ethylenedioxythiophene (EDOT) in a water solution of hydroxypropyl cellulose (HPC) as a polymer lyotropic liquid crystal (LC) gives polyEDOT*/HPC hybrid (PEDOT*/HPC) as an optically active polymer. Circular differential interference contrast (C-DIC) microscopy of the polymer reveals a well-resolved ordered structure, and circular dichroism (CD) measurements indicate a Cotton effect for the polymer film. PEDOT prepared using this chiral nematic LC field exhibits good el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
59
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 42 publications
(45 reference statements)
0
59
0
Order By: Relevance
“…44 Convincingly instance demonstrated that by covalent attachment of functional groups at the conjugated backbone could obtain novel properties and applications. To achieve chirality of the resulting polymer, different substituted EDOTs bearing chiral glycols, 40,45 chiral octyloxycarbonyl group, 38 L-leucine,…”
Section: Liqi Dong and Baoyang Lu Contributed Equally To This Workmentioning
confidence: 99%
See 2 more Smart Citations
“…44 Convincingly instance demonstrated that by covalent attachment of functional groups at the conjugated backbone could obtain novel properties and applications. To achieve chirality of the resulting polymer, different substituted EDOTs bearing chiral glycols, 40,45 chiral octyloxycarbonyl group, 38 L-leucine,…”
Section: Liqi Dong and Baoyang Lu Contributed Equally To This Workmentioning
confidence: 99%
“…38 Enantiomeric molecules exhibit mirror imaged CD spectra of opposite sign. A mono-signate CD of (R)-and (S)-PEDTM-PP films in the doped and dedoped state were illustrated in Figure 5.…”
Section: Spectramentioning
confidence: 99%
See 1 more Smart Citation
“…HPC in solvent as a polymer CLC system can be conveniently applicable for electrochemical polymerization. HPC was used as a template for production of polymers [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Electrochemical polymerization is a useful and convenient method that produces a polymer film on the electrode surface [16,17]. The polymers prepared by asymmetric electrochemical polymerization display intense circular dichroism (CD) in the reduced state, and weaker CD in the oxidized state [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%